Creating Markets in Rwanda : Transforming for the Jobs of Tomorrow - International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
Rwanda has made unsurmountable strides along its development path. Rwanda has placed among the world’s fastest-growing economies, climbing the development ladder from second-poorest in the world in 1994 to sit ahead of nineteen other countries. Today, job creation lies at the heart of Rwanda’s development challenge. The government of Rwanda (GoR) recognizes the urgency of creating new jobs. The new thirty-year Vision for the period up to 2050, which is currently being finalized, elaborates the country’s long-term development goals. The core of transformation for prosperity is developing high-value and competitive sectors, to transition the population and economy from subsistence agriculture toward industry and high-skilled services. The purpose of the Rwanda country privates sector diagnostic (CPSD) is to identify market opportunities and constraints in sectors that advance the country’s development objectives. By assessing the landscape of private sector investment in the country, the CPSD identifies specific constraints to private sector investment and productivity growth, concrete opportunities that could materialize in the short term, and the reforms that will enable this materialization. It then discusses how specific actions by the public sector in collaboration with the private sector by filling gaps in public investment, reforming regulations, and addressing market failures could unleash sectors’ private investment potential.